Model Tata Kelola dan Perilaku Bisnis Stand/Booth Container di Provinsi Jambi - Tona Aurora Lubis; Syahmardi Yacob; Firmansyah Firmansyah (J-MAS (Jurnal Manajemen dan Sains), 2021)
Street food business phenomenon gives a new touch in the culinary industry of Jambi Province because of the unique way of selling that does not use stalls or tents, but uses a knock down cart in the form of a box shaped like a container, so it is known as stand /Booth Container. The ultimate goal of this research is to formulate a model of governance and business behavior of stand/booth containers in Jambi Province. This study used mixed methods (qualitative and quantitative methods) using the type of Sequal Exploratory Design. The result conluded that the business behavior of food outlets/containers in Jambi Province which is reflected by efficiency, innovation, creativity, and creativity affects business performance which is reflected by capital growth, profit growth, and sales growth. In contrast, governance as reflected by modern, partnership and systematic does not affect business performance which is reflected by capital growth, profit growth and sales growth.